(untitled) (World Economics and Finance Bulletin, 2026)
Foreign direct investment (FDI) plays a key role in the development of national and regional economies, contributing to technological modernization, employment growth, and integration into global markets. However, FDI inflows are unevenly distributed across a country, leading to regional differentiation. Analyzing this differentiation makes it possible to identify the factors of regional investment attractiveness, assess imbalances, and develop effective regional policies. The article examines modern methods and tools for analyzing the regional differentiation of foreign direct investment (FDI) attraction. It reveals the essence of the uneven distribution of investment flows across regions and identifies the key factors determining differences in their investment attractiveness